Pengaruh motivasi belajar terhadap hasil belajar di SD Negeri Sanggrahan 2 - tarmiyati, Nia (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of learning motivation on student learning outcomes at SD Negeri Sanggrahan 2 for the academic year 2020/2021. Motivation is everything that can affect success in learning activities. Learning will be difficult to reach an optimal point without motivation. This study uses a descriptive correlation which is carried out to study the problems of fourth grade elementary school students in knowing how much the level of motivation influences student learning outcomes in elementary school in grade IV SD Negeri Sanggrahan 2 as a sample in this research. In collecting data, it can be done by using an instrument questionnaire of the motivation variable and student test results as the average variable for the achievement of student success. the data processing is done by calculating the statistics and the average correlation. The data shows an explanation of the high level of reliability and the magnitude of the influence of learning motivation on learning outcomes where calculated = 3.26 and table = 1.73, with a significant level of 0.05 meaning Ha is accepted and Ho is rejected, and so the conclusion is that there is an effect of motivational outcomes on learning outcomes in elementary school.